Effect of Parish Development Model in Enhancing Social Inclusion in Rwerere Town Council Rukungiri District. - Karuhanga, Jeremiah (Kabale University, 2024)
This study examined the effect of the Parish Development Model in enhancing social inclusion in Rwerere Town Council, Rukungiri District and it was guided by the following specific objectives; to assess the level of community engagement within the Parish Development initiatives in Rwerere Town Council, Rukungiri District, to identify challenges hindering effective social inclusion through the Parish Development Model in Rwerere Town Council, Rukungiri District and suggest strategies for enhancing social economic transformation through improved implementation strategies within the Parish Development framework in Rwerere Town Council, Rukungiri District. The study adopted a descriptive research design. The researcher used the descriptive research design as appropriate for the study because the study was concerned with finding answers to key questions. The Population of this study comprised of 60 teenage girls, 45 parents, and 15 guardians in Rubuguri Town Council, Kisoro District (120 in total) because they are the basis of the study and this provided the relevant answers to the study questions. For this to be achieved, the researcher used Krejcie and Morgan's table of determining sample size from a given target population to get a sample size of 92 who represented the whole target population under study. Descriptive analysis was used to determine the proportions and frequency of the variables. The study revealed that PDM involves local residents actively participating in identifying their needs and priorities as represented by 20% of the respondents. The findings revealed that to enhance effective social inclusion through the Parish Development Model in Rwerere Town Council. There are insufficient training programs available under the PDM that focus on empowering marginalized groups such as youth and women with relevant skills for economic engagement. The study revealed that improving implementation strategies also requires investing in capacity building for local leaders and community members. They argued that training programs focused on financial literacy, agricultural best practices, and entrepreneurship can empower individuals to effectively utilize resources available through the PDM as this accounted for 12%. The study recommends organizing monthly or quarterly meetings that allow community members to voice their opinions, share experiences, and provide feedback on ongoing projects. This will foster a sense of ownership and encourage active participation. The study also recommended engaging local leaders and influencers who can motivate community members to participate in development initiatives. Their involvement can bridge gaps between the government and the community, ensuring that voices are heard.